The impact of mixing modes on reliability in longitudinal studies - Alexandru Cernat (University of Essex, Institute for Social and Economic Research (ISER), 2013)
Mixed mode designs are increasingly important in surveys and large longitudinal studies are progressively moving to or considering such a design. In this context our knowledge regarding the impact of mixing modes on data quality indicators in longitudinal studies is sparse. This study tries to ameliorate this situation by taking advantage of a quasi-experimental design in a longitudinal survey. Using models that estimate reliability for repeated measures, quasi-simplex models, 33 variables are analysed by comparing a single mode CAPI design to a sequential CATI-CAPI design. Results show no differences in reliabilities and stabilities across mixed modes either in the wave when the switch was made or in subsequent waves. Implications and limitations are discussed.
Keywords: C81; C83; 330; longitudinal survey; mixed mode survey; CAPI; CATI; reliability; quasi-simplex models; latent Markov chains